One-plasmid double-expression His-tag system for rapid production and easy purification of MS2 phage-like particles - Mikel, Pavel; Vasickova, Petra; Kralik, Petr (Scientific reports, 2017)
MS2 phage-like particles (MS2 PLP) are artificially constructed pseudo-viral particles derived from bacteriophage MS2. They are able to carry a specific single stranded RNA (ssRNA) sequence of choice inside their capsid, thus protecting it against the effects of ubiquitous nucleases. Such particles are able to mimic ssRNA viruses and, thus, may serve as the process control for molecular detection and quantification of such agents in several kinds of matrices, vaccines and vaccine candidates, drug delivery systems, and systems for the display of immunologically active peptides or nanomachines. Currently, there are several different in vivo plasmid-driven packaging systems for production of MS2 PLP. In order to combine all the advantages of the available systems and to upgrade and simplify the production and purification of MS2 PLP, a one-plasmid double-expression His-tag system was designed. The described system utilizes a unique fusion insertional mutation enabling purification of particles using His-tag affinity. Using this new production system, highly pure MS2 PLP can be quickly produced and purified by a fast performance liquid chromatography (FPLC) approach. The system can be easily adapted to produce other MS2 PLP with different properties.
Keywords: virové plášťové proteiny; virion; Levivirus; Capsid Proteins; Recombinant Fusion Proteins; Plasmids; Virion; plazmidy; rekombinantní fúzní proteiny